Ambient oxidation of Ti3C2 MXene initialized by atomic defects. Issue 48 (3rd December 2019) - Xia, Fanjie; Lao, Junchao; Yu, Ruohan; Sang, Xiahan; Luo, Jiayan; Li, Yu; Wu, Jinsong
Abstract : The mechanism of Ti3 C2 -MXene ambient oxidation has been revealed by electron microscopy, disclosing the effects of defects and Ti-ion diffusion. Abstract : MXenes are a group of two-dimensional transition metal carbides/nitrides that have been widely used for many useful applications such as energy storage, catalysis and sensors. For large scale applications of MXenes, the ambient stability is a critical issue. However, the detailed degradation mechanism of MXenes remains largely unclear. Here, the oxidation mechanism of MXene flakes under ambient conditions has been studied using aberration corrected scanning transmission electron microscopy (STEM). The heterogeneous growth of titanium oxide has been observed in the vicinity of atomic defects on the MXene basal plane as well as on the edges of MXene flakes. C atoms are oxidized at Ti-vacancies to form amorphous carbon aggregations, while Ti cations are oxidized at the nearby sites with atomic steps/edges. The diffusion of both electrons and Ti cations is involved and the Ti-ion diffusion is prompted by an internal electric field intrinsically built up during oxidation. The anatase TiO2 nanoparticles preferentially grow along the {101} lattice plane. A loose orientation relationship between the anatase TiO2 and MXene was identified, showing that mostly the {101} plane of TiO2 nanocrystals is perpendicular to the Ti3 C2 -MXene {0001} basal plane. This work reveals at atomic resolution the oxidation mechanism of MXenes under ambient conditions and will shed light on the design and synthesis of more stable MXenes. It may also provide insights to develop a one-step method to synthesize hybrid structures of carbon supported TiO2 nanoparticles for future large scale applications.